Analisa dan Perbandingan Performa Tools Forensik Digital pada Smartphone Android menggunakan Instant Messaging Whatsapp - Ilhami Algi Plianda; Rini Indrayani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Technology services are currently developing rapidly, one of the services that rapidly increased is the development of Instant messaging (IM) technology which is increasingly sophisticated and cannot be separated from people's lives. However, the use of this technology is not always about activities that have a good impact but are also vulnerable to being used as a medium to do harmful things. One of the things that have a detrimental impact that often occurs is cybercrime by utilizing Instant messaging (IM) applications. One of the IM platforms that is often used as a media for cybercrime is WhatsApp. The message deletion feature can be one of the feature that uses criminals to hide evidence of a crime. Therefore, a digital forensic protocol is needed that can help the authorities to uncover evidence of crimes that have been tried to eliminate by criminals. Therefore, this study raises the issue of research utilizing the Whatsapp platform using two tools, namely MOBILedit and Oxygen Forensic. The final result of this research is a method and tool recommendation that can be the best alternative for digital forensics needs.